2023
DOI: 10.1186/s43094-023-00485-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of self-emulsifying drug delivery system-based lipsticks loaded with ketoconazole

Abstract: Background Self-emulsifying system-based lipstick may prove to have the potential of enhancing moisturizing characteristics and delivering hydrophobic drug antifungal drugs for the management of lip fungal infection, especially candidiasis. In this study, the self-emulsifying drug delivery system (SEDDs) of ketoconazole was obtained using IPM (Oil), Tween 80 (surfactant), and PEG 400 (co-surfactant). The medicinal lipstick was developed from the SEDDs, and the concentration of waxes (beeswax an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Literature review has revealed previous successful attempts at using many plant oils including oilive, castor palm kernel, coconut seed oils and palm oils as the lipid phase of SEDDS [9,10,11].…”
Section: Original Research Articlementioning
confidence: 99%
“…Literature review has revealed previous successful attempts at using many plant oils including oilive, castor palm kernel, coconut seed oils and palm oils as the lipid phase of SEDDS [9,10,11].…”
Section: Original Research Articlementioning
confidence: 99%